Diagnostics of laser induced graphite plasma under various pressures of air, helium and argon - Haider, Zuhaib (Penerbit UTM Press, 2016)
Laser induced plasma provides information about the elemental composition of sample surface and through spectroscopy vital information about plasma dynamics can be obtained. In this paper we present the diagnostics of laser induced plasma at various pressures of Air, Helium and Argon gases. Graphite sample was ablated with Q-smart 850 laser while spectra were captured Plasma parameters have been calculated by using well known methods based on Saha and Boltzmann equations. Plasma temperature was calculated relative intensity of ionic carbon lines CII 251.21 nm and CII 426.73 nm while the electron density was determined by using spectroscopic information of CI 247.85 nm and CII 426.73 nm emission lines in Saha equation. Plasma temperature and electron density were found to be dependent upon nature and pressure of the ambient atmosphere. Higher temperatures and electron densities were obtained in the presence of Air as ambient environment that is attributed to electrical and physical properties of the Air. Keeping into consideration the plasma expansion in various environments the selection of a suitable ambient pressure can be made on the basis of spectral diagnostics of plasma for a particular laser energy to obtain desirable plasma temperature and electron density suited for certain applications.